Decomposição assistida por radiação micro-ondas e ultravioleta para posterior determinação de níquel, vanádio e enxofre em coque de petróleo - Oliveira, Jussiane Souza da Silva de (2013)
The presence of Ni, V and S in petroleum coke is undesirable because can cause poisoning in catalysts used in refining processes and problems during the coke burning such as SOX emissions, abrasion and fouling of the combustion chambers. Considering the impact caused by these contaminants, it becomes necessary to determine impurities such as Ni, V e S in petroleum coke. In this work, a method for the determination of Ni, V and S in petroleum coke by inductively coupled plasma optical emission spectrometry (ICP OES) after microwave-assisted UV digestion (MW-UV-AD) was proposed. The decomposition of petroleum coke by MW-UV-AD was performed using an electrodeless discharge lamps, positioned inside quartz vessels, which were initiated and maintained by the microwave field. The following conditions for the decomposition of petroleum coke by MW UV-AD were evaluated: HNO3 concentration (1, 4, 7, 10 and 14.4 mol L-1), volume of H2O2 (30%, 1 and 3 mL) sample weight (100, 250 and 500 mg), heating time program (40 and 60 min) and the use of ultraviolet (UV) radiation lamps. In all tests, the solution volume was kept in 15 mL. By using solution (4 mol L-1 HNO3 or higher) the agreement to reference values was better than 98% for Ni, V and S. Reference values were obtained by decomposition of petroleum coke by microwave-induced combustion and further determination of Ni, V and S by ICP OES. With the use of UV lamp and HNO3 4 mol L-1 with 3 mL H2O2 was possible to decompose up to 500 mg of petroleum coke (60 min of heating, residual carbon content, RCC < 21%). The results were in agreement better than 96% for Ni, V and S compared to the reference values. Using UV lamps lower RCC values were obtained when compared to those without UV lamps. The accuracy of the proposed method was evaluated by the decomposition of certified reference material (NIST 2718, Green Petroleum Coke) and the results were better than 96% for all analytes. The limits of quantification using 500 mg of sample were 0.62, 0.39 and 25.4 μg g -1 for Ni, V and S, respectively. The combination of microwave heating with UV was considered suitable for the decomposition of petroleum coke, using only diluted solution HNO3 and H2O2.